Non-destructive Testing of a 100-Year-Old Reinforced Concrete Flat Slab Bridge - Wolert, Patryk J.; Kolodziejczyk, Marek K.; Stallings, J. Michael; Nowak, Andrzej S. (Frontiers in Built Environment, 2020)
Nondestructive tests and field measurements were used to establish the structural details and behavior of a 100-year-old reinforced concrete flat slab bridge. There are no structural drawings of the bridge, its reinforcing details, or records from the time of its original construction. The purpose of this project was to identify the structural details necessary to model the bridge for a determination of its load capacity. This paper discusses the methods used to accomplish this purpose. Live load tests were performed to investigate the overall behavior of the bridge. A finite element model of one span of the 11-span bridge was developed in ABAQUS. Measured strains and deflections served as a basis for calibration of the finite element model. Comparisons of the finite element analysis and live load test results are presented.